2019
DOI: 10.1177/2050312119858248
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment to amputation and interest in upper limb transplantation

Abstract: Objective: Upper limb transplantation provides a new restorative option for individuals with amputations. As true for most operations, patient selection is critical to optimizing transplantation outcomes. To improve on the patient selection process, we used qualitative methods to better understand the issues regarding upper extremity loss as well as upper limb transplantation from the amputee point of view. Methods: Individuals with upper limb amputations (age range = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…We found that some participants had not explored other treatment options, such as VCA, because of concerns about financial burden or lack of insurance coverage. Our findings are consistent with Talbot et al (2019) who found that adjustment to amputation (limb loss) was inversely related to an interest in transplantation and concluded this may help explain the difficulty in identifying and selecting candidates for VCA. One possible solution for addressing concerns about financial burden or insurance coverage is to have clearer communication early in the evaluation or treatment process about financial burdens and what insurance will and will not cover.…”
Section: Discussionsupporting
confidence: 92%
“…We found that some participants had not explored other treatment options, such as VCA, because of concerns about financial burden or lack of insurance coverage. Our findings are consistent with Talbot et al (2019) who found that adjustment to amputation (limb loss) was inversely related to an interest in transplantation and concluded this may help explain the difficulty in identifying and selecting candidates for VCA. One possible solution for addressing concerns about financial burden or insurance coverage is to have clearer communication early in the evaluation or treatment process about financial burdens and what insurance will and will not cover.…”
Section: Discussionsupporting
confidence: 92%
“…Talbot and colleagues found an inverse relationship between patients' interest in UE VCA and adjustment time since amputation. 31 Patients also reported identity concerns of transforming into "Frankenstein" 52 through VCA, as found elsewhere. 53 Other study participants desired further information before deciding, 17 including about costs and insurance coverage, as documented elsewhere.…”
Section: Discussionmentioning
confidence: 54%
“…15 A few studies have examined factors influencing interest in UE VCA, albeit using small samples. [29][30][31] No research has examined how individuals make decisions about whether to pursue UE VCA or patients' perceptions of informed consent for UE VCA.…”
mentioning
confidence: 99%
“…Efforts are being made to study hand and upper extremity transplant recipients and caregivers outside of laboratory settings. 14 Herrington et al explored the narratives of caregivers who often felt burdened by demands of providing care, 15 despite their being crucial for long-term patient well-being and allograft survival. 16 Caregiving imposes physical and psychosocial demands on caregivers that affect their health and well-being sufficiently to impact the care they provide.…”
Section: Commentarymentioning
confidence: 99%